MENAKAR KEMASLAHATAN REKSADANA SYARIAH DALAM PERSPEKTIF MAQASHID SYARIAH - Iqbal, M; Muttaqin, Faisal; Zuhro, Fatimatuz; Rachmania, Rachmania (I-Economics, 2020)
Benefit is the main indicator for Islamic economic principles. In developing sharia-based financial institutions, all companies are competing to provide their best products based on the benefit for the mankind. An investment is a way for the people to get their benefits for living. The objective of investment is two-way relationship between the investor and the company. For another side, the investment is a financial management that teaches people to prepare for a better future, on the other side the investment helps financial institutions to obtain capital in developing Islamic financial institution products so that They can make a real contribution for the national development. This research tries to analyze the phenomenon of the Islamic capital market before and during the pandemic of Covid-19, by measuring the benefits of sharia mutual funds in the perspective of maqashid sharia which aims to protect religion, maintain reason, protect the soul, protect offspring, and protect property with literacy about the benefit for the mutual funds of sharia, hopefully this study will be an alternative and solution for the people to invest in order to achieve the highest achievement (falah) in the world and the here after.